2021
DOI: 10.1080/21505594.2021.1898777
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane domains of type III-secreted proteins affect bacterial-host interactions in enteropathogenic E. coli

Abstract: Many bacterial pathogens utilize a specialized secretion system, termed type III secretion system (T3SS), to translocate effector proteins into host cells and establish bacterial infection. The T3SS is anchored within the bacterial membranes and contains a long needle/filament that extends toward the host-cell and forms, at its distal end, a pore complex within the host membrane. The T3SS pore complex consists of two bacterial proteins, termed SctB and SctE, which have conflicting targeting indications; a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 81 publications
3
13
0
Order By: Relevance
“…We observed that the TMD2-exchanged variants, which showed reduced secretion, were enriched in the bacterial membrane compared with Tir wt -V5 and TMD1-exchanged variants ( Figure 2A ). This result is in line with our previous report showing that replacement of the translocator TMDs with an alternative hydrophobic sequence resulted in their mislocalization into the bacterial membrane ( Gershberg et al., 2021 ). Interestingly, the Tir- EscD1 -V5 variant did not display enriched membrane localization, despite containing the only TMD sequence of an actual membrane protein.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We observed that the TMD2-exchanged variants, which showed reduced secretion, were enriched in the bacterial membrane compared with Tir wt -V5 and TMD1-exchanged variants ( Figure 2A ). This result is in line with our previous report showing that replacement of the translocator TMDs with an alternative hydrophobic sequence resulted in their mislocalization into the bacterial membrane ( Gershberg et al., 2021 ). Interestingly, the Tir- EscD1 -V5 variant did not display enriched membrane localization, despite containing the only TMD sequence of an actual membrane protein.…”
Section: Discussionsupporting
confidence: 93%
“…While the mechanism underlying this targeting discrimination remains largely unknown, recent studies have suggested that a major factor is the moderate hydrophobicity of the TMDs of these secreted proteins, which is sufficient for integration into eukaryotic cell membranes but is not recognized by the bacterial signal recognition particle ( Krampen et al., 2018 ). This was recently demonstrated by our group, where replacement of the TMDs of EPEC translocators (EspB and EspD) with a more hydrophobic sequence resulted in their mislocalization into the bacterial membrane and abolished their secretion ( Gershberg et al., 2021 ). In addition, the ability of Tir to escape the co-translational pathway and membrane integration mechanism was previously suggested to be mediated through interaction with its chaperone, CesT ( Elliott et al., 1999 ).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations